Molecular weight-gyration radius relation of globular proteins: a comparison of light scattering, small-angle X-ray scattering and structure-based data - Smilgies, Detlef-M.; Folta-Stogniew, Ewa (Journal of applied crystallography, 2015)
The molecular weight–gyration radius relation for a number of globular proteins based on experimental light scattering data is compared with small‐angle X‐ray scattering data recently published by Mylonas & Svergun [J. Appl. Cryst. (2007), 40, s245–s249]. In addition, other recent experimental data and theoretical calculations are reviewed. It is found that the MW–Rg relation for the globular proteins is well represented by a power law with an exponent of 0.37 (2).